2021
DOI: 10.1063/5.0073629
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of activation method and temperature to III-nitride micro-light-emitting diodes with tunnel junction contacts grown by metalorganic chemical vapor deposition

Abstract: The optical and electrical characteristics of InGaN blue and green micro-light-emitting diodes (μLEDs) with GaN tunnel junction (TJ) contacts grown by metalorganic chemical vapor deposition (MOCVD) were compared at different activation temperatures among three activation methods from the literature, namely, sidewall activation, selective area growth (SAG), and chemical treatment before sidewall activation. The devices with chemical treatment before activation resulted in uniform electroluminescence and higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…It has been shown that 20 × 20 µm 2 micro-LEDs with TJ contact have better peak EQE, as well as maximum WPE, than the device with ITO contact by employing chemical treatment before thermal activation via sidewalls, as shown in the year 2021 data point of figure 3, which is the first demonstration that micro-LEDs with MOCVD TJ contact can outperform ITO devices in terms of EQE and WPE [34]. The better efficiency is attributed to greater optical power, but the current-voltage characteristic of the TJ device requires more attention to reduce the voltage penalty compared to the ITO device [41]. It is anticipated that the activation processes will become more mature and develop to address the voltage penalty issue in MOCVD-grown TJs, and the activation mechanism can be further understood via empirical and simulation work.…”
Section: Advances In Science and Technology To Meet Challengesmentioning
confidence: 90%
See 1 more Smart Citation
“…It has been shown that 20 × 20 µm 2 micro-LEDs with TJ contact have better peak EQE, as well as maximum WPE, than the device with ITO contact by employing chemical treatment before thermal activation via sidewalls, as shown in the year 2021 data point of figure 3, which is the first demonstration that micro-LEDs with MOCVD TJ contact can outperform ITO devices in terms of EQE and WPE [34]. The better efficiency is attributed to greater optical power, but the current-voltage characteristic of the TJ device requires more attention to reduce the voltage penalty compared to the ITO device [41]. It is anticipated that the activation processes will become more mature and develop to address the voltage penalty issue in MOCVD-grown TJs, and the activation mechanism can be further understood via empirical and simulation work.…”
Section: Advances In Science and Technology To Meet Challengesmentioning
confidence: 90%
“…For micro-LEDs with TJ contacts grown by MOCVD, several activation methods, including activation via sidewalls and selective-area growth of TJs, have been demonstrated to facilitate hydrogen diffusion out of the passivated p-GaN. It has been shown that the activation conditions, such as annealing temperature and activation approach, have strong impacts to the optical and electrical performances [41]. Because of the small device sizes, the distance of hydrogen diffusion is comparable to the device dimension, where sidewall activation can be effective to result in great electrical characteristic.…”
Section: Advances In Science and Technology To Meet Challengesmentioning
confidence: 99%
“…After, buried tunnel junction (BTJ) apertures with 30nm heights were etched using reactive ion etching (RIE). Then, all samples were annealed at 730C in a N2/O2 environment for 30min to activate the p-/p++-GaN 10 . Finally, 1,810nm n-GaN ([Si] = 6×10 18 cm -3 ) and 1,700nm UID GaN were regrown on top of the BTJ apertures.…”
Section: Methodsmentioning
confidence: 99%
“…Sidewall was treated with a KOH solution. 3,4,12,13,20,21) Three pairs of SiO 2 and Ta 2 O 5 stacks with a 30 nm Al 2 O 3 cap layer were deposited by ion beam deposition. Thirty nm SiO 2 was deposited by atomic layer deposition (ALD) for the sidewall passivation.…”
mentioning
confidence: 99%
“…17 29) In this work, our ultra-small InGaN-based amber μLEDs demonstrate a much more robust EQE, which is related to proper fabrication processes such as ALD SiO 2 sidewall passivation and KOH sidewall treatment. 3,4,12,20,21) Therefore, InGaN material has obvious advantages over AlInGaP material for ultra-small size red/ amber μLEDs.…”
mentioning
confidence: 99%